2015
DOI: 10.4236/jssm.2015.86084
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Milk Supply and Marketing Chains and Losses in Wolmera and Ejere Districts of Ethiopia

Abstract: This study was made with the purposes of characterizing milk supply and marketing chains, postproduction losses of milk, and evaluating the potential of supply chain management approach to reduce milk losses in Ethiopia. Primary data were collected by semi-structured survey questionnaire and interview of key informants. The collected data were analyzed using SPSS and Microsoft Excel sheets. Mapping, characterizations, and descriptive statistics were used to analyze the collected data. Both quantitative and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…The current results showed that the total milk postharvest loss at farm level was in disagreement with the results of FAO ( 2005), which reported that the total milk postharvest loss at farm level was estimated to be 6.5% of the milk available in Tanzania. The current findings showed that the total milk post-harvest losses in Addis Ababa-Selale concur with the findings of Tadesse et al (2015), who reported that the milk postharvest losses occurring at the cooperative/union stage was 39% identified as loss hotspots in the dairy value chain in Ejere and Wolmera districts.…”
Section: Estimated Milk Post-harvest Losses Along the Milk Sheds And ...supporting
confidence: 89%
See 1 more Smart Citation
“…The current results showed that the total milk postharvest loss at farm level was in disagreement with the results of FAO ( 2005), which reported that the total milk postharvest loss at farm level was estimated to be 6.5% of the milk available in Tanzania. The current findings showed that the total milk post-harvest losses in Addis Ababa-Selale concur with the findings of Tadesse et al (2015), who reported that the milk postharvest losses occurring at the cooperative/union stage was 39% identified as loss hotspots in the dairy value chain in Ejere and Wolmera districts.…”
Section: Estimated Milk Post-harvest Losses Along the Milk Sheds And ...supporting
confidence: 89%
“…Refrigerators are more effective than other methods at reducing milk postharvest losses. The majority of respondents did not use cooling devices (refrigerators) as mitigation strategies, which is slightly consistent with the finding of Tadesse et al (2015), who reported that smallholder dairy producers were 95% did not use cooling devices for milk storage in Ejere and Wolmera districts.…”
Section: Mitigation Strategies Of Milk Post-harvest Losses Along Milk...supporting
confidence: 84%
“…e current study identi ed four types of strategies that were used in the milk procurement procedures and helped maintain the existing relationships between collectors and producers, such as a simple contract agreement, an incentive-based system, creating fair value share, and building trust (Figure 4). According to [3], in the Oromia region and the southern part of Ethiopia, hardly any formal contractual agreements exist between milk collectors and producers. Everything was based on trust, and there were no formal contractual agreements and advanced payments.…”
Section: Discussionmentioning
confidence: 99%
“…ey select their buyers based on the ultimate share in the pro t, trust-based relationships, and lack of alternatives to access another buyer. Also, price, delivery convenience, and business relationships were indicated as some criteria in the buyer selection decision [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantial improvement in the aquaculture sector, very few studies have so far been conducted to identify the fish value chain actors and their value addition decision, preferably for Rui, Labeo rohita, Catla, Catla catla, Tilapia, Oreochromis nilotica, and Pangas, Pangasius hypophthalmus (Alam, 2011;Alam et al, 2012;Amentae, 2016;Chowdhury et al, 2012;Hossain, 2011;Islam et al, 2014;Obiero et al, 2019;Tola, 2014). Therefore, we have addressed the following research questions in this study: (i) who were the actors in the Rui, Catla, Tilapia, and Pangas fish value chain, and how were they linked in the value chain process?…”
Section: Introductionmentioning
confidence: 99%